2017
DOI: 10.3389/fphys.2017.00397
|View full text |Cite
|
Sign up to set email alerts
|

Managing Thoracic Aortic Aneurysm in Patients with Bicuspid Aortic Valve Based on Aortic Root-Involvement

Abstract: Bicuspid aortic valve (BAV) can be both sporadic and hereditary, is phenotypically variable, and genetically heterogeneous. The clinical presentation of BAV is diverse and commonly associated with a high prevalence of valvular dysfunction producing altered hemodynamics and aortic abnormalities (e.g., aneurysm and dissection). The thoracic aortic aneurysm (TAA) in BAV frequently involves the proximal aorta, including the aortic root, ascending aorta, and aortic arch, but spares the aorta distal to the aortic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…Bicuspid aortic valve (BAV) is associated with aortic dilation, 1 with up to 50% of patients with BAV developing ascending aortic aneurysms (AsAAs). 2 This is attributed to altered hemodynamics resulting in an eccentric helical flow pattern. 3 , 4 Hemodynamics coupled with genetic or developmental defects are implicated in aberrant remodeling of the aortic wall relative to individuals with a tricuspid aortic valve (TAV).…”
mentioning
confidence: 99%
“…Bicuspid aortic valve (BAV) is associated with aortic dilation, 1 with up to 50% of patients with BAV developing ascending aortic aneurysms (AsAAs). 2 This is attributed to altered hemodynamics resulting in an eccentric helical flow pattern. 3 , 4 Hemodynamics coupled with genetic or developmental defects are implicated in aberrant remodeling of the aortic wall relative to individuals with a tricuspid aortic valve (TAV).…”
mentioning
confidence: 99%
“…However, AoR dilation may be an inherent form of BAV associated disease and a heterogeneous disease compared with tubular mid-ascending aortic dilatation, confirming the speculation of Cotrufo et al 16) Aortic annulus enlargement that responses to AoR stretch occur in AoR dilation, leading to AR. 18) The heterogeneity of BAV aortopathy was elaborated by Norton et al, 19) and they believed that AoR dilation and AR should be treated more aggressively during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Both inherent disposition and abnormal hemodynamics were proved as criminals in the development of BAV-associated aortic dilatation, the different specific phenotypes of aortic dilation may be dominated by one main factor, and others (even some unknown reasons) are accomplices. 5,16,19) Our dominance analysis may imply that (1) inherent disposition was mainly responsible for the higher frequency of AoR+AAo dilation and lower prevalence of AAo+PArc dilation in patients of Type-1 LR with AR or AS+AR; (2) in patients with Type-0 LAT and AS, valve-related hemodynamics may be the determinant for the bias prevalence of different types of aortic dilation (more AAo+PArc and less AoR+AAo), and (3) the higher prevalence of AAo dilation may be attributed to both of above two variables in patients with Type-1 LR and AS.…”
Section: Discussionmentioning
confidence: 99%
“…European Society of Cardiology guidelines recommend that surgery should be performed in patients with a bicuspid aortic valve with a maximal diameter ≥55 mm 56. Meanwhile, however, Norton and Yang7 have emphasized the importance of aortic root phenotype in bicuspid aortic valve and have suggested that diameters of the root exceeding 45 mm should be indications for surgery.…”
Section: Introductionmentioning
confidence: 99%